Pre-treatment and electroless Ni–P deposition for surface-modification of tungsten fibres. (4th May 2017) - Yuan, Z.; Liang, S.; Zhuo, L.
Abstract : In order to improve the surface activity of tungsten fibres (Wf ) for subsequent sintering with adjacent powders of W and Cu, autocatalytic Ni–P coatings on Wf were fabricated via electroless deposition in this work. Before electroless deposition, optimal pre-treatment of Wf was determined to increase their surface activity without destroying their internal structure. Afterwards, the deposition rate, microstructure and phase constituents of the plated Ni–P coatings at bath pH values of 5, 6, 7, 8 and 9 were studied systematically. SEM observations showed the presence of uniform and compact grains in the coating and XRD analysis revealed their amorphous or partially crystalline structure. Further sintering of Wf with powders of W and Cu demonstrated the superior interfacial bonding state due to the Ni–P coatings on the Wf surface.